1, 10‐Phenanthroline Carboxylic Acids for Preparation of Functionalized Metal‐Organic Frameworks. Issue 11 (16th October 2019) - Abel, Anton S.; Yu Mitrofanov, Alexander; Yakushev, Aleksei A.; Zenkov, Ilya S.; Morozkov, Gleb V.; Averin, Alexei D.; Beletskaya, Irina P.; Michalak, Julien; Brandès, Stéphane; Bessmertnykh‐Lemeune, Alla
Abstract: Synthetic approaches to 1, 10‐phenanthroline‐3‐carboxylic acid (2 ), 1, 10‐phenanthroline‐3, 8‐dicarboxylic acid (3 ) and their functionalized derivatives were investigated. Acids 2 and 3 were prepared in good yields from bromophenanthrolines via palladium‐catalyzed alkoxycarbonylation. Moreover, butyl 8‐bromo‐1, 10‐phenanthroline‐3‐carboxylate was obtained in acceptable yield (25–35%) by ceasing the carbonylation of the dibromide 5 after 30–70% consumption of the starting compound. To prepare functionalized derivatives of acids 2 and 3, the reactions of butyl 8‐bromo‐1, 10‐phenanthroline‐3‐carboxylate and diethyl 4, 7‐dichloro‐1, 10‐phenanthroline‐3, 8‐dicarboxylate with various nucleophiles were investigated. SN Ar reactions are suitable for the synthesis of 4, 7‐diazido‐, dimethoxy‐ and diamino‐substituted 3, 8‐bis(ethoxycarbonyl)phenanthrolines, including the macrocyclic derivatives. The bromine atom at position 8 of the phenanthroline ring reacts with nucleophiles only in the presence of the palladium catalysts. The scope of these reactions was briefly investigated conducting Sonogashira, Suzuki‐Miyaura and Hirao reactions. Hydrolysis of the functionalized esters of phenanthroline leads to corresponding acids in good yields. Abstract : Synthetic approaches to 1, 10‐phenanthroline‐3‐carboxylic acid, 1, 10‐phenanthroline‐3, 8‐dicarboxylic acid and their functionalized derivatives were developed using Pd‐catalyzed reactions and catalyst‐free nucleophilic substitution reactions.